A study of the histories and inspirations behind selections of songs from the soprano repertoire - Knoles, Katherine Louise (Kansas State University, 2018)
The purpose of this graduate report is to explore the influential stories and historical aspects behind the composition of selected works from the soprano repertoire. This document is completed in partial fulfillment of the requirements for the Master of Music degree in vocal performance. The recital was held on Sunday, April 29, 2018, at seven-thirty o’clock in the evening at the First Presbyterian Church, located on 801 Leavenworth Street in Manhattan, KS. Works for this recital were chosen to create a contrasting and unique program to span the soprano repertoire from the Baroque era to late twentieth century, and to display the histories and influences of these compositions. The following works are examined in detail within this document: 1. “Komm in mein Herzenhaus” from Ein’ feste Burg ist unser Gott, BWV 80, by Johann Sebastian Bach 2. “On mighty pens” from The Creation by Franz Joseph Haydn 3. Fêtes galantes I (1882) by Claude Debussy 1. “En sourdine” 2. “Fantoches” 3. “Clair de lune” 4. “Senza mama” from Suor Angelica by Giacomo Puccini 5. As it fell upon a day by Aaron Copland 6. A Letter from Sullivan Ballou by John Kander 7. “What Good Would the Moon Be?” from Street Scene by Kurt Weill 8. Les filles de Cadix by Léo Delibes Each chapter of this document is dedicated to a specific work from the program, and contains the following: 1) biographical information on the composer, 2) historical information and influences on the composition as well as from its grander counterpart if the selection is from a larger work, and 3) a textual and musical analysis of the selection.
Keywords: Histories; Soprano; Suor Angelica; Sullivan Ballou; Delibes; Madame Vasnier